Deteksi Dini dan Pendampingan Keluarga pada Usia Dua Tahun (BADUTA) Beresiko Stunting di Desa Klepu, Kecamatan Pringapus, Kabupaten Semarang - Isri Nasifah; Maksum (UNIVERSITAS NGUDI WALUYO, 2023)
Stunting is one of the problems that hinder human development globally. Currently there are around 162 million children under the age of five experiencing stunting. Presidential Regulation Number 72 of 2021 concerning the Acceleration of Stunting Reduction that is holistic, integrative and of good quality through coordination, synergy and synchronization among stakeholders. Early detection and assistance to families at risk of stunting involves family members and caregivers. The family is taught how to monitor growth and development and manage babies under two years of age (BADUTA) who are at risk of becoming not at risk of stunting. This service is carried out in three stages, namely: assessment, analysis and implementation, monitoring and evaluation. All processes have been carried out well and have a very large meaning in the increase in the community regarding early detection of stunting and a decrease in the number of BADUTA who are at risk of stunting which is marked by an increase in the ability of parents/caregivers to provide, process, serve food ingredients and increase the appetite of BADUTA ABSTRAK Stunting merupakan salah satu masalah yang menghambat perkembangan manusia secara global. Pada saat ini terdapat sekitar 162 juta anak berusia dibawah lima tahun mengalami stunting. Peraturan Presiden Nomor 72 Tahun 2021 tentang Percepatan Penurunan Stunting yang holistik, integratif, dan berkualitas melalui koordinasi, sinergi, dan sinkronisasi di antara pemangku kepentingan. Deteksi dini dan pendampingan pada keluarga berisiko stunting melibatan anggota keluarga dan pengasuh. Keluarga tersebut diajarkan cara memantau pertumbuhan dan perkembangan serta mengelola bayi usia di bawah dua tahun (BADUTA) yang beresiko menjadi tidak berisiko stunting. Pengabdian ini dilaksanakan dengan tiga tahap yaiti : pengkajian, analisis dan implementasi, monitoring dan evaluasi. Semua proses telah terlaksana dengan baik serta memberikan arti sangat besar adanya peningkatan masyarakat tentang deteksi dini stunting dan adanya penurunan jumlah BADUTA yang beresiko stunting yang ditandai dengan peningkatan kemampuan orang tua/pengasuh penyediaan, pegolahan, penyajian bahan makanan serta bertambahnya nafsu makan BADUTA.